Density and temperature diagnostics of solar emission lines from Na vii and Al ix - Raju P.K.; Dwivedi B.N.; Gupta A.K. (My University, 2025)
Line intensity ratios of EUV emission lines from Na vii and Al ix have been considered for electron density and temperature determinations within the chromosphere-corona transition region and the corona. The electron pressure within the emission region has been assumed to be a constant parameter. Theoretical line intensities for these ions have been computed using a model solar atmosphere and compared with the values as observed by ATM ultraviolet spectrometer. The observed intensities correspond to the average quiet-Sun conditions near solar minimum. © 1994 Kluwer Academic Publishers.